Norstictic Acid Is a Selective Allosteric Transcriptional Regulator - Garlick, Julie M. (2021)
Inhibitors of transcriptional protein–protein interactions (PPIs) have high value both as tools and for therapeutic applications. The PPI network mediated by the transcriptional coactivator Med25, for example, regulates stress-response and motility pathways, and dysregulation of the PPI networks contributes to oncogenesis and metastasis. The canonical transcription factor binding sites within Med25 are large (∼900 Å2) and have little topology, and thus, they do not present an array of attractive small-molecule binding sites for inhibitor discovery. Here we demonstrate that the depsidone natural product norstictic acid functions through an alternative binding site to block Med25–transcriptional activator PPIs in vitro and in cell culture. Norstictic acid targets a binding site comprising a highly dynamic loop flanking one canonical binding surface, and in doing so, it both orthosterically and allosterically alters Med25-driven transcription in a patient-derived model of triple-negative breast cancer. These results highlight the potential of Med25 as a therapeutic target as well as the inhibitor discovery opportunities presented by structurally dynamic loops within otherwise challenging proteins.